Advanced treatment of urban wastewater by sand filtration and graphene adsorption for wastewater reuse: Effect on a mixture of pharmaceuticals and toxicity. Issue 1 (March 2015) - Rizzo, L.; Fiorentino, A.; Grassi, M.; Attanasio, D.; Guida, M.
Graphical abstract: Highlights: Sand filtration coupled with graphene for pharmaceuticals removal from wastewater. Pharmaceuticals removal from wastewater by graphene adsorption higher than 95%. Graphene adsorption effectively decreased wastewater toxicity to Daphnia magna . Graphene did not significantly affect phyto-toxicity. Graphene removed pharmaceutical mixture better (96%) than GAC (62%). Abstract: Pharmaceuticals removal from urban wastewater by coupling conventional sand filtration with graphene adsorption reactor (GAR) was investigated. During GAR regime phase, the percentage removal of the four investigated pharmaceuticals, (namely caffeine, carbamazepine, ibuprofen and diclofenac) was higher than 95% (98.2, 97.0, 95.5 and 97.0%, respectively). In spite of the high initial concentrations of the target pharmaceuticals (10 mg/L each) and 4 months of experimentation (62 days of adsorption treatment), typical breakthrough adsorption curves were not observed. Graphene adsorption treatment effectively decreased toxicity to Daphnia magna (0–50% immobilization), but only a slight improvement in germination index (phyto-toxicity tests) was observed after GAR treatment. Finally, graphene performances were compared with conventional (granular activated carbon) adsorption process, and the best performance in the removal of pharmaceutical mixture was quite poor (62% in terms of UV absorbance) compared to GAR (96%).